2009
DOI: 10.1063/1.3067871
|View full text |Cite
|
Sign up to set email alerts
|

The formation of light emitting cerium silicates in cerium-doped silicon oxides

Abstract: Cerium-doped silicon oxides with cerium concentrations of up to 0.9 at. % were deposited by electron cyclotron resonance plasma enhanced chemical vapor deposition. Bright cerium related photoluminescence, easily seen even under room lighting conditions, was observed from the films and found to be sensitive to film composition and annealing temperature. The film containing 0.9 at. % Ce subjected to anneal in N2 at 1200 °C for 3 h showed the most intense cerium-related emission, easily visible under bright room … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
40
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 19 publications
9
40
1
Order By: Relevance
“…We have previously reported on the photoluminescence and structure of Tb and Ce-doped silicon rich silicon oxides (SRSO) and oxygen rich silicon oxides (ORSO) (17,18). The luminescent behavior of Tb-doped ORSO and SRSO samples considered in this work is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously reported on the photoluminescence and structure of Tb and Ce-doped silicon rich silicon oxides (SRSO) and oxygen rich silicon oxides (ORSO) (17,18). The luminescent behavior of Tb-doped ORSO and SRSO samples considered in this work is summarized in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The sample compositions are given in Table 1. Further details of the deposition system, film growth and structure have previously been discussed (16)(17)(18). Post-deposition, the films were subjected to high temperature annealing in a quartz tube furnace under flowing N 2 at temperatures up to 1200 C for 60 minutes.…”
Section: Sample Fabrication and Processingmentioning
confidence: 99%
“…However, there are some drawbacks for some conventional synthesis processes. For example, these are incompatible with standard Si processing technologies [3]. Furthermore, some research has demonstrated that the luminescence properties of Ce ions varied as materials were prepared via different processes, and there is yet no doubtless conclusion about the relationship between the luminescence properties and the environment structures.…”
Section: Introductionmentioning
confidence: 99%
“…This situation contradicts the fact that the radiative oxide defects tend to be eliminated during annealing process. Furthermore, in view of the forementioned relationship between the PL intensity and Ce concentrations, therefore, the Ce 3þ ions are the major contributors to this broad PL band which is the characteristic emissions of 5d [3,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation